Pentingnya Transparasi: Kurangnya Komunikasi di Perusahaan PT Garuda Indonesia (Persero) Tentang Kisruh Lepkuei Garuda dan OJK Mengenai Analisis Laporan Keuangan - Harmen, Hilma; Wati, Aprina; Ajwa, Isna Firdasari; Nurbani, Kharisma; Lubis, Melani Catherine M; Harahap, Nadya Viska; Simanullang, Richard Josua; Telaumbanua, Rizky Idaman (Ikatan Da'i Indonesia, 2024)
This journal reveals issues at PT Garuda Indonesia (Persero) due to a lack of communication involving the Lapkeu Garuda turmoil, which implicates the OJK (Financial Services Authority), primarily stemming from miscommunication problems between the OJK and Garuda Indonesia's management. Insufficient communication adversely impacts the company's performance and results in inaccurate and non-transparent financial reporting. Utilizing a qualitative literature review method, this research investigates various relevant literature sources on the topic. The study aims to explore the significance of transparency concerning the communication deficit at PT Garuda Indonesia (Persero), particularly regarding the Lapkeui Garuda turmoil and the OJK's role in financial statement analysis. This journal provides practical implications, indicating that transparency in financial reporting is not only an obligation but also a long-term investment for sustainability and company growth. The company needs to enhance both internal and external communication and improve collaboration with regulators to ensure adequate transparency in financial information dissemination. Collaborative efforts will aid in restoring stakeholder trust, reducing reputation risks, and establishing a strong foundation for sustainable business growth.